2019
DOI: 10.3389/fpsyg.2019.01821
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Physical Activity Are Associated With the Motivational Climate and Resilience in University Students of Physical Education From Andalucía: An Explanatory Model

Abstract: Background The practice of Physical Activity (PA) is a key factor for the improvement of physical and mental health, making the study of the motivational processes that take part in the development of active lifestyles of interest. Methods This cross-sectional study was conducted on 775 university students of Physical Education (PE) from Spain. This research aims to develop an explanatory model for the relationships between motivational climate and resilience according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
5
18
0
3
Order By: Relevance
“…Similar outcomes were reached by Szu-Ying, Heng-Hsin, Li-Ning, Liang-Kung, Ching-Iy, and Yen-Ling, [35] in their study, concluding that greater resilience was associated with higher amounts of physical exercise. These findings are also corroborated by Chacón-Cuberos, Castro-Sánchez, Pérez-Turpin, Olmedo-Moreno, and Zurita-Ortega [36] who, when addressing the second hypothesis proposed by their study, showed greater resilience in university students engaging in more than 180 min of weekly physical activity.…”
Section: Discussionsupporting
confidence: 74%
“…Similar outcomes were reached by Szu-Ying, Heng-Hsin, Li-Ning, Liang-Kung, Ching-Iy, and Yen-Ling, [35] in their study, concluding that greater resilience was associated with higher amounts of physical exercise. These findings are also corroborated by Chacón-Cuberos, Castro-Sánchez, Pérez-Turpin, Olmedo-Moreno, and Zurita-Ortega [36] who, when addressing the second hypothesis proposed by their study, showed greater resilience in university students engaging in more than 180 min of weekly physical activity.…”
Section: Discussionsupporting
confidence: 74%
“…Se puede revelar entonces que el desarrollo deportivo en el juego de los deportes individuales (sin incluir deportes de combate) presenta cierta menor necesidad de respuestas flexibles cambiantes que los colectivos o deportes de combate, repercutiendo en su resiliencia y favoreciendo respuestas más ajustadas al ambiente. En cualquier caso, sería interesante conocer el clima motivacional de los deportistas, lo cual puede ofrecer un significado, ya que como se sabe, un clima orientado a la tarea desarrolla la resiliencia en los atletas (Chacón-Cuberos et al, 2019).…”
Section: Discussionunclassified
“…Moreover, if we compare physically active and non-active students, the first ones will be able to overcome the challenges with less difficulty and effort together with higher guarantees of success. This is a consequence of a higher PF level ( Dollman et al, 2005 ; Dumith et al, 2011 ; Rauner et al, 2013 ; Schutte et al, 2016 ; Wang et al, 2016 ; Palou et al, 2019 ; Riso et al, 2019 ), which will give them greater enjoyment and satisfaction in practice ( Dudley et al, 2011 ; Gillison et al, 2013 ; Chacón-Cuberos et al, 2019 ; Sierra-Díaz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a complement to the concern and importance of PA practice, current research focuses on combined studies with fitness levels (PF) ( Ruiz et al, 2011 ; Rauner et al, 2013 ; Henriksson et al, 2016 ; Schutte et al, 2016 ; Wang et al, 2016 ; Palou et al, 2019 ; Riso et al, 2019 ; Tomkinson et al, 2019 ; López-Gil et al, 2020 ), and also including other variables such as obesity ( Ness et al, 2007 ; Steele et al, 2009 ; Ekelund et al, 2011 ; Collings et al, 2013 ; Rauner et al, 2013 ; Benítez-Porres et al, 2016b ; Henriksson et al, 2016 ; Fang et al, 2017 ; Palou et al, 2019 ), eating habits ( Agostinis-Sobrinho et al, 2018 ; Ramírez-Vélez et al, 2018 ; López-Gil et al, 2020 ), physical self-concept or body image ( Fernández-Bustos et al, 2019 ; Onetti-Onetti et al, 2019 ), and the motivational climate ( Chacón-Cuberos et al, 2018a , b , 2019 ; Castro-Sánchez et al, 2019 ; Zurita-Ortega et al, 2019 ), among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation